System classification and certification of electronic trading platforms - T. R. Torpishchev (Вестник университета, 2024)
The article purpose is to develop criteria for certification of marketplaces based on the most significant classifications.   Within the framework of the study, the existing classifications are presented, the relationship between them is analyzed. Based on the review of classifications and economic analysis, a mechanism for the certification of commodity marketplaces has been developed: the criteria for certification, the form of the marketplace passport and the appendix to the passport with the main economic indicators have been highlighted. As an approbation, the certification of the Ozon marketplace (Internet Resheniya) has been carried out. On the basis of public reporting, an appendix with the main economic indicators has been completed. The results of the work will be of interest to researchers of bilateral markets, investors, potential and current marketplaces participants in the context of the digital transformation of the economy and the growth of e-commerce in Russia. The vectors obtained as a result of the certification process can be used to compare Russian product marketplaces not only with each other, but also with foreign platforms.